The anti-proliferative effect of a bergamot juice extract and its flavanones in leukemic THP-1 cell line involves SIRT2 - Alessandro Maugeri; Caterina Russo; Laura Musumeci; Michele Navarra (Atti della Accademia Peloritana dei Pericolanti - Classe di Scienze Medico-Biologiche, 2025)
Plant kingdom provides a wide plethora of remedies which can be exploited to treat prevent and manage human ailments, among which cancer. In these regards, there is consistent supporting evidence of the beneficial properties of Citrus fruits, which are consumed worldwide. Among these, pharmacological effects of Citrus bergamia Risso (bergamot) have been extensively demonstrated, including anticancer ones, which are due to its elevated flavonoid content. Recently, the flavonoid-rich extract of bergamot juice (BJe) its main flavanones have been investigated for their anti-leukemic activity in THP-1 cells, a model of acute myeloid leukaemia (AML). Specifically, it was shown that BJe and its main flavanones were able to hamper viability of leukemic cells, along with blocking cell cycle in triggering apoptosis. Noteworthy, it has been suggested that in AML there is an over-expression of SIRT2, an enzyme belonging to the family of sirtuins. Interestingly, it has been shown that BJe and its main flavanones can inhibit the deacetylase activity of SIRT2 in the isolated enzyme and in THP-1 cells, where they also reduced its gene expression. Moreover, docking simulations clarified that the main flavanones, namely naringenin and hesperetin, were able to interact with the catalytic core of SIRT2 in a similar manner as the synthetic inhibitor SirReal2. These results support the anti-leukemic potentiality of BJe, along with its main flavanones, highlighting that SIRT2 is involved in these effects.